Growth and Production Potential of Anogeissus latifolia Based Silvo-pastoral System Under Different Pruning Managements - Rai, P.; Ramana, D.B.V.; Rao, G.R.; Yadav, R.S.; Singh, U.P. (Indian Journal of Agroforestry, 2020)
Growth and production potential of three-years-old Anogeissus latifolia based silvo-pastoral system was studied where Chrysopogan fulvus was as a grass component and Stylosanthes hamata as a legume component. The treatments comprise of pruning intensity (25%, 50% and 75% of the total height of the tree) and control (unpruned trees with pasture and pasture without trees). Increase in pruning intensity from 25 to 75 per cent increased the tree height and decreased the collar diameter where as no effect was found on dbh. Pruning intensity did not have any significant effect on forage production, but pruning seems to be essential for better establishment and growth of understorey pasture. The forage production under unpruned trees was significantly (P< 0.05) lower than pruned trees. The A. latifolia based silvo-pastoral system has greatest potential in degraded lands in terms of forage, top fodder and fuel wood production and nutritive value of the pruned foliage.